2017
DOI: 10.1128/mbio.00870-17
|View full text |Cite
|
Sign up to set email alerts
|

Type II Secretion Substrates ofLegionella pneumophilaTranslocate Out of the Pathogen-Occupied Vacuole via a Semipermeable Membrane

Abstract: Legionella pneumophila replicates in macrophages in a host-derived phagosome, termed the Legionella-containing vacuole (LCV). While the translocation of type IV secretion (T4S) effectors into the macrophage cytosol is well established, the location of type II secretion (T2S) substrates in the infected host cell is unknown. Here, we show that the T2S substrate ProA, a metalloprotease, translocates into the cytosol of human macrophages, where it associates with the LCV membrane (LCVM). Translocation is detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 102 publications
0
38
0
3
Order By: Relevance
“…Thus, the absence of galectin-8 upon knockdown could explain the enhanced replication of Legionella (27). An association of galectin-8 with the LCVs of infected human macrophages at 6 h postinfection was previously validated, strengthening the putative role as a danger receptor (99).…”
Section: Discussionmentioning
confidence: 86%
“…Thus, the absence of galectin-8 upon knockdown could explain the enhanced replication of Legionella (27). An association of galectin-8 with the LCVs of infected human macrophages at 6 h postinfection was previously validated, strengthening the putative role as a danger receptor (99).…”
Section: Discussionmentioning
confidence: 86%
“…maltophilia VirB/D4 T4SS triggers apoptosis of human macrophages in a contact-dependent manner. When we extended our analysis to include infection of U937 cells, a human macrophage line that is widely used for infection studies (74,(94)(95)(96), the virB10 mutant attached to the host cells at a wild-type level ( Fig. S3B) but resulted in less cell death (i.e., more viable host cells) than did the wild-type strain (Fig.…”
Section: Figmentioning
confidence: 99%
“…It has also been shown that T2SS mutants trigger immune response pathways, like MyD88 and Toll Like receptor 2, resulting in an increase in inflammatory cytokine levels and suggesting T2SS effector proteins dampen cytosolic innate immunity sensors [118,120]. A recent study by Truchan et al elucidated the cellular localization of 2 T2SS effectors, ProA (a metalloproteinase) and ChiA (chitinase), which escape the LCV and then form a ring-like pattern around the LCV membrane in the host cell cytosol [121].…”
Section: The Type II Secretion System (T2ss)mentioning
confidence: 99%
“…These studies help to shift views from the predominant paradigm in the L. pneumophila field, which is that only type 4 secretion system (T4SS) effectors are able gain access to the host cell cytoplasm during infection [121].…”
Section: The Type II Secretion System (T2ss)mentioning
confidence: 99%